Measuring Efficiency in Agile Software Design Methodologies - Woźniak, Krzysztof (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents theoretical and methodological considerations in matters of efficiency in software project development teams which use agile methodologies. In the contemporary literature, those methodologies are described as a universal solution to all organisational problems faced by managers of large teams working on complex IT projects. This article attempts to answer the question of the extent to which agile software development methodologies fulfill the conditions of the classical methodological efficiency. I suggest that even when using agile design methodology, managers should attempt to operationalise the basic parameters describing the efficiency and effectiveness of the team. This will allow them to make effective decisions based on facts, not assumptions and hunches.